2006
DOI: 10.1097/01.ccm.0000221922.08878.49
|View full text |Cite
|
Sign up to set email alerts
|

From evidence to clinical practice: Effective implementation of therapeutic hypothermia to improve patient outcome after cardiac arrest*

Abstract: Objective-The coagulation and inflammatory cascades may be linked in the pathogenesis of acute lung injury and acute respiratory distress syndrome. However, direct evidence for the contribution of abnormalities in coagulation and fibrinolysis proteins to outcomes in patients with acute lung injury/acute respiratory distress syndrome is lacking.Design-Retrospective measurement of plasma levels of protein C and plasminogen activator inhibitor-1 in plasma samples that were collected prospectively as part of a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
230
7
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 502 publications
(260 citation statements)
references
References 63 publications
(30 reference statements)
14
230
7
9
Order By: Relevance
“…There have also been several previous studies with historical controls [25][26][27] considered as GOE IV, and experimental studies. [28][29][30][31] Recently, several observational studies, with historical controls [32][33][34][35] (GOE IV), uncontrolled studies 36,37 (GOE V) and a European registry 39 (GOE V), all show that MTH is feasible, safe, has few side effects and seems to contribute toward improved survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have also been several previous studies with historical controls [25][26][27] considered as GOE IV, and experimental studies. [28][29][30][31] Recently, several observational studies, with historical controls [32][33][34][35] (GOE IV), uncontrolled studies 36,37 (GOE V) and a European registry 39 (GOE V), all show that MTH is feasible, safe, has few side effects and seems to contribute toward improved survival.…”
Section: Resultsmentioning
confidence: 99%
“…20 Recently, observational studies 32,34 (GOE IV) and two registry reports 39,40 (GOE V) have reported the feasibility of treating patients with non-VF cardiac arrest. Although the prognosis for this group of cardiac-arrested patients is worse, 39 recent survival data on non-VF patients are promising 38 (GOE V).…”
Section: Which Patients To Cool?mentioning
confidence: 99%
“…In einer Registerarbeit mit mehr als 6000 Patienten nach Kreislaufstillstand war eine Hypotonie (SBD <90 mmHg) zum Zeitpunkt der Aufnahme auf die ICU mit einem schlechteren Outcome vergesellschaftet [855]. Ein gutes Outcome konnte in Studien mit Patienten erreicht werden, die nach präklinischem Kreislaufstillstand in eine Klinik aufgenommen wurden, wenn der MAP zwischen mindestens 65-75 mmHg [630] und höchs-tens 90-100 mmHg [633,670] lag. Aufgrund fehlender definitiver Daten soll der Ziel-MAP so eingestellt werden, dass eine ausreichende Urinproduktion (1 ml/kgKG und /h) sowie eine normale oder fallende Plasmalaktatkonzentration erreicht werden können.…”
Section: Herz-kreislauf-systemunclassified
“…In den ersten 48 h nach Kreislaufstillstand ist eine hypertherme Phase typisch (Hyperpyrexie; [696,697,698] [709]. Sechs Studien mit historischen Kontrollgruppen wiesen den Nutzen der therapeutischen Hypothermie bei komatösen Überlebenden eines präklinischen Kreislaufstillstands aufgrund aller EKG-Rhythmen nach [630,633,710,711,712,713]. Zwei nichtrandomisierte Studien mit gleichzeitig durchgeführten Kontrollen deuten auf einen möglichen Nutzen der Hypothermie nach einem präklinischen und innerklinischen Kreislaufstillstand infolge anderer initialer Herzrhythmen hin [714,715].…”
Section: Temperaturkontrolleunclassified
“…12,23 The goals of care after cardiac arrest are described in Table 1. 14 Post-cardiac arrest patients have varied clinical manifestations of altered neurologic, cardiovascular, and metabolic function.…”
Section: Management Of Post-cardiac Arrest Syndromementioning
confidence: 99%